Real-time Implementation of a Full State Feedback Controller for a DC Motor - K. Love; C. Kriger; N. Tshemese-Mvandaba (International Journal of Electrical Engineering and Applied Sciences)
This research work presents the real-time implementation of a Full State Feedback (FSFB) controller, which controls the angular position of a Direct Current (DC) motor. The designed Simulink controller is transformed into an object that is used in Beckhoff’s TwinCAT programming environment to interface with an actual DC motor test rig. The MATLAB command code required for the transformation is described with all other software required. The test rig used for the implementation is also shown and discussed. Lastly, a case study is done to test the control system’s response and limitations to various positional set point changes. This research contributes to the study of FSFB control for DC motors by providing a practical method to implement the simulated controller on a hardware device that is used in industry. The implemented control system can be used in industry and not just for testing purposes. This method can be used to implement any designed FSFB controlled DC motor model.